Cost structure and profitability of oyster farming in Panay, Capiz - Baes, Jese B. (2002.)
The study focused on the economic analysis of oyster farming; particularly productivity, costs and returns, income, and employment aspects as they relate to different farm sizes, and methods of culture in Panay, Capiz. A total of 27 oyster farmers were interviewed. Results revealed that the value of production per farm was estimated at P50,855, greatest in Butacal and least in bantigue. By farm size, it appeared that the small farms were more efficient per unit area. The combination of broadcast, stake and hanging methods yields the highest crop per farm. Oysters harvested from the farm were primarily sold. About 5 were given away to friends, relatives, or paid for services, and family members consumed only 2 ., Consisting mostly of boat/raft and plots farm investment was relatively low in Agojo/Tanza Norte than in other farm sites. Butacal had the largest investment of P49,803 per farm. Investment per unit area was relatively less for the bigger farms. The hanging method required the least investment while the broadcast with stake appeared to be the most costly. Hired labor and food were the major variable inputs, depreciation accounted for fixed cost and opportunity cost primarily included opportunity cost of investment. Total expenses per farm averaged P5,623. By farm size, total costs were lower in larger oyster farms. As the farm size increased, expenses also increased while per unit area decreased with increasing farm size. Oyster farmers using the broadcast with stake method incurred the largest farm expenses. Gross income was estimated at P49,961 per year. A direct relationship between farm size and gross income exists. By method of culture, the combination of broadcast, stake and hanging methods earned the highest gross income. The same relationships as that for the gross income were observed in the analysis of the net income. On the average, an oyster farmer received a gross profit of P49,727 and a pure profit of P 45,232. Gross and pure profit increased with farm size. The combination of broadcast, stake and hanging methods earned the highest pure profit of P79,511. Small-sized farms and farms that used the hanging method received negative pure profits. The study recommends that the government should take steps to improve the performance of the farms especially with the low-income farm sites and should seek ways of advancing the socioeconomic condition of oyster farmers. Likewise the municipal governments should properly implement the monitoring of oyster farms to check the socioeconomic conditions, the plans of the oyster farmers, and the obstacles they encountered toward improvement of their business. Researches directed at enhancing the productivity levels of oyster farming should be given priority. Oyster farming being part-time activity must be complemented with programs that encourage alternative income sources.
Research Paper (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Oyster farming -- Panay, Capiz